2009
DOI: 10.1371/journal.pone.0007215
|View full text |Cite
|
Sign up to set email alerts
|

Functional, Non-Clonal IgMa-Restricted B Cell Receptor Interactions with the HIV-1 Envelope gp41 Membrane Proximal External Region

Abstract: The membrane proximal external region (MPER) of HIV-1 gp41 has several features that make it an attractive antibody-based vaccine target, but eliciting an effective gp41 MPER-specific protective antibody response remains elusive. One fundamental issue is whether the failure to make gp41 MPER-specific broadly neutralizing antibodies like 2F5 and 4E10 is due to structural constraints with the gp41 MPER, or alternatively, if gp41 MPER epitope-specific B cells are lost to immunological tolerance. An equally import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 79 publications
4
39
0
Order By: Relevance
“…This result might be linked to a differential strength of signalling between IgM a BCR and IgM b BCR for proliferation/survival of peritoneal B-cells. Such specific interactions with IgM a (but not IgM b ) determinants have been already reported with the HIV-1 envelope gp41 membrane proximal external region [26]. Furthermore, the phenotype of mature B-cells differs between the various mouse substrains.…”
Section: Resultssupporting
confidence: 51%
“…This result might be linked to a differential strength of signalling between IgM a BCR and IgM b BCR for proliferation/survival of peritoneal B-cells. Such specific interactions with IgM a (but not IgM b ) determinants have been already reported with the HIV-1 envelope gp41 membrane proximal external region [26]. Furthermore, the phenotype of mature B-cells differs between the various mouse substrains.…”
Section: Resultssupporting
confidence: 51%
“…We previously demonstrated that two bnAbs (2F5, 4E10) directed at the HIV-1 Env gp41 neutralizing site near the viral membrane are autoreactive (13, 83), and in bnAb antibody heavy and light chain knock-in mice, both bnAbs were shown to be controlled by multiple immune tolerance mechanisms (21, 22, 24, 84, 85). The observations of bnAb autoreactivity prompted the hypothesis that patients with systemic lupus erythematosus (SLE) will be able to make bnAbs more readily than others during chronic HIV-1 infection (15).…”
Section: Discussionmentioning
confidence: 99%
“…Some bnAbs are restricted during early B-cell development at the first tolerance checkpoint in bone marrow due to germline B-cell receptor (BCR) autoreactivity, resulting in fewer bnAb precursors before vaccination (21, 22, 24, 84, 85), while other bnAb germline BCRs are not autoreactive, and autoreactivity is only acquired in the periphery during affinity maturation (90). BnAbs with long third heavy chain complementarity determining regions that do emerge in HIV-1 infection appear to be rare by virtue of tolerance mechanisms that reduce their precursor frequency (12, 26, 91).…”
Section: Discussionmentioning
confidence: 99%
“…Primary labeled mAbs used were Pacific Blue, allophycocyanin, or Texas Red-conjugated anti-B220 (clone RA3–6B2), phycoerythrin (PE)–Cy7 anti-CD19, fluorescein isothiocyanate (FITC)–conjugated anti-IgD (clone 11–26), FITC-conjugated anti-IgG2b (clone R12-3), FITC-, allophycocyanin-, or PE-Cy7–conjugated anti-IgM (clone 15F9), PE-conjugated anti-CD21, and PE-Cy7–labeled anti-CD23 (eBioscience). Flow cytometric analysis of B cell reactivity for the MPER 2F5 epitope was performed similarly using single-cell splenocyte suspensions from naïve and immunized 2F5 mature and 2F5 UA dKI mice that were stained with MPER (SP62) tetramers, also as previously described (17, 22, 48). IgG2b- and IgM-specific analysis was performed using an intracellular staining protocol based on the BD Cytofix/Cytoperm fixation/permeabilization method.…”
Section: Methodsmentioning
confidence: 99%